Advances in hospitality and leisure. vol. 18 - Chen, Joseph S. (Advances in hospitality and leisure ;, 2023)
Advances in Hospitality and Leisure (AHL), a peer-reviewed research journal, has been published annually since 2004. AHL is indexed in Scopus and included in the Australian Business Deans Council (ABDC) journal quality list. Its editors, editorial board members, ad-hoc reviewers entail scholars from North America, Europe and Asia-Pacific. AHL with international in focus attempts to divulge the innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected in the context of hospitality, tourism, and leisure. It strives to address the needs of the populace willing to disseminate seminal ideas, concepts, and theories derived from scholarly inquiries. AHL covers full papers and research notes in the matter of conceptual models and empirical investigations using inductive and deductive methods. The authors of this publication come from and Africa, America, Asia/Pacific, Europe, and Middle East. Potential readers may retrieve useful articles to outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the new subjects of learning.